Efektivitas Digital Marketing, Desain Produk, dan Harga dalam Membentuk Keputusan Pembelian Konsumen Sepatu Futsal Ortuseight - Anung Prabaningtyas; Guruh Taufan Hariyadi , Bara Zaretta , Aries Setiawan (Program Pascasarjana STIE Amkop Makassar, 2025)
This study aims to evaluate the extent to which digital marketing, product design, and price influence consumer purchasing decisions of Ortuseight futsal shoes. The research approach is quantitative with a survey method through a questionnaire aimed at Ortuseight consumers. Data analysis was carried out using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. Testing includes evaluation of measurements (validity and reliability) and evaluation of structural models to test relationships between variables. The results of the study show that the three variables, namely digital marketing, product design, and price, have a positive impact on purchasing decisions. Product design is the most dominant factor, highlighting the importance of an attractive and trend-relevant look in attracting consumer interest. Digital marketing has proven to be effective in increasing consumer awareness and interest, although further optimization is needed in audience targeting. Meanwhile, prices have a significant influence, although it is recommended that companies develop more flexible pricing strategies to reach a wider market segment. This study confirms that the combination of digital marketing, product design, and competitive pricing plays a crucial role in increasing the effectiveness of Ortuseight's marketing strategy.